Evidence-Based Guideline on Critical Patient Transport and Handover to ICU - Tesfaye Belaneh Agizew; Henos Enyew Ashagrie; Habtamu Getinet Kassahun; Mamaru Mollalign Temesgen (Anesthesiology Research and Practice)
The perioperative period is a time in which significant physiological change occurs. Improper transfer of information at this point can lead to medical errors. Planning and preparation for critical patient transport to ICU is vital to prevent adverse events. Critical patient transport to ICU must be as safe as possible and should not cause additional risks. It needs good communication, planning, and appropriate staffing with standard monitoring. Evidence shows inconsistency and variability on the use of standardized protocols during critical patient transfer and handover to the ICU. There is a variety of controversial approaches about the need of sedation, use of end-tidal CO2 monitoring, and manual versus mechanical ventilation based on different evidence. The objective of this review was to recommend safer options of critical patient transfer to the ICU that help reduce patient morbidity and mortality. Methods. Google Scholars, PubMed through HINARI, and other search engines were used to search high-quality evidence that help reach appropriate conclusions. Discussion. Critical patient transfer and handover to ICU is a complex procedure that needs experienced hands, availability of appropriate team members, standard monitoring, and necessary emergency and patient-specific medications. Appropriate and adequate transfer of patient information to the receiving team decreases patient morbidity and mortality when the transfer team uses standardized checklist. Conclusion. Involvement of senior physicians, use of standard monitoring, and appropriate transfer of information have been shown to decrease critical patient morbidity and mortality.